VIOLENCE AGAINST BLACK PEOPLE IN BRAZIL AND STRUCTURAL RACISM: REFLECTIONS OF THE PAST AND CONTEMPORARY REPRODUCTIONS - Reis Azarias, Clodoaldo; Sacomori, Luciana; Cristina dos Santos Nunes, Nara; Reis Azarias, Natan; Maria Machado de Oliveira, Neusa; Emed Alves, Simone (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes structural violence against the Black population in Brazil, understood as a legacy of slavery and coloniality, which persists and reproduces itself in contemporary social practices. Structural racism manifests itself in exclusion, discrimination, and marginalization, affecting dimensions such as labor, education, health, security, and access to justice. The study adopts a qualitative and bibliographic methodology, engaging with authors such as Silvio Almeida, Achille Mbembe, Aníbal Quijano, Abdias Nascimento, Sueli Carneiro, and Milton Santos. The analysis demonstrates that structural racism is sustained by historical and institutional logics that produce inequality and legitimize symbolic and material violence. It concludes that overcoming this scenario requires effective public policies, affirmative actions, and a decolonial epistemological repositioning.